Development of a free radical scavenging bacterial consortium to mitigate oxidative stress in cnidarians. Issue 5 (14th July 2021) - Dungan, Ashley M.; Bulach, Dieter; Lin, Heyu; van Oppen, Madeleine J. H.; Blackall, Linda L.
Summary: Corals are colonized by symbiotic microorganisms that profoundly influence the animal's health. One noted symbiont is a single‐celled alga (in the dinoflagellate family Symbiodiniaceae ), which provides the coral with most of its fixed carbon. Thermal stress increases the production of reactive oxygen species (ROS) by Symbiodiniaceae during photosynthesis. ROS can both damage the algal symbiont's photosynthetic machinery and inhibit its repair, causing a positive feedback loop for the toxic accumulation of ROS. If not scavenged by the antioxidant network, excess ROS may trigger a signaling cascade ending with the coral host and algal symbiont disassociating in a process known as bleaching. We use Exaiptasia diaphana as a model for corals and constructed a consortium comprised of E. diaphana –associated bacteria capable of neutralizing ROS. We identified six strains with high free radical scavenging (FRS) ability belonging to the families Alteromonadaceae, Rhodobacteraceae, Flavobacteriaceae and Micrococcaceae . In parallel, we established a consortium of low FRS isolates consisting of genetically related strains. Bacterial whole genome sequences were used to identify key pathways that are known to influence ROS. Abstract : The field of coral microbiome engineering is in its infancy and is currently limited by a lack of definitive information about the functional roles of cnidarian microbiome members. Outlined in this manuscript is the start of a complex process to identify, evaluate, and select durable and useful candidate consortium members that may buffer the coral host against climate warming. We identified six diverse bacterial strains with high free radical scavenging (FRS) ability and six conspecific/congeneric low FRS strains with a view to including them in an inoculum to mitigate the effects of thermal stress in cnidarians.